PENGARUH TEKNOLOGI INFORMASI DAN MODAL MANUSIA TERHADAP PEREKONOMIAN DI INDONESIA - Zulkifli Zulkifli; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims to examine information technology and human capital to economic in Indonesia with the selected model is the Random Effect Mpdel (REM). The data used is panel data the period 2013-2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies.The variables use are information technology, education,, dan health. The research method used is Ordinary Least Square (OLS). The estimation results show that are information technology, education and health have a positive and significant effect on the economic growth in Indonesia. Meanwhile simultaneously Technology information, education, an health affect the economic in Indonesia.